Mixed-integer second-order cone programming taking appropriate approximation for the unit commitment in hybrid AC–DC grid - Zhou, Bo; Ai, Xiaomeng; Fang, Jiakun; Wen, Jingyu; Yang, Jianhua (Journal of engineering (Stevenage, England), 2017)
With the rapid development and deployment of voltage source converter based high-voltage direct current, the traditional power system is evolving to the hybrid AC–DC grid. New optimisation methods are urgently needed for these hybrid AC–DC power systems. In this study, mixed-integer second-order cone programming (MISOCP) for the hybrid AC–DC power systems is proposed. The second-order cone relaxation is adopted to transform the AC and DC power flow constraints to MISOCP. Several IEEE test systems are used to validate the proposed MISCOP formulation of the optimal power flow and unit commitment in the hybrid AC–DC power systems.